Analisis Metode Economic Value Added (Eva) Dan Return On Assets (Roa) Dalam Meningkatkan Kinerja Keuangan Pt.Telekomunikasi Indonesia Tbk Periode 2012-2015 Yang Terdaftar Di Bursa Efek Indonesia (Bei) - Retnowati, Mia; , Lukman Hakim, S.E., M.Si (2017)
The purpose of this study was conducted to determine significant and positive financial performance of the telecomunication company that went public in the period 2012-2015 and knowing the signs of the onset of the economic added value and the value of overall profit used to predict financial performance in obtaining economic value added and value overall profit is the method of economic value added and return on assets. To determine the economic value added and value value overall profit using eight financial ratios namely Net Income to Interest After Taxes, Total Debt and and Equity to Debt Short Term, Total Debt to Total Debt and Equity, Expense Taxes on Income Before Taxes, Net Profit After Tax to Total Assets. The sample used in this study were Telekomunikasi Indonesia Tbk in 2012 showed an increase in the economic value added and value of overall profit. In 2013 showed a decrease of the economic added value and the value of overall profit. In 2014-2015 showed an increase in the economic economic value added and value of overall profit. For four consecutive years in good condition and showed a positive financial performance and significant.